Effects of cover crops on soil water, the supply of carbon to the system and the yield of soybean in different environments. - Capurro, J. E. (Universidad Nacional del Litoral, 2022)
Effects of cover crops on soil water, the supply of carbon to the system and the yield of soybean in different environments. The sustainability of agricultural environments in the Humid Argentine Pampean Region is affected by the monoculture of soybean (Glycine max (L.) Merr.). The low efﬁciency in the use of environmental resources during fallows and its negative effect on the sustainability and productivity of production systems makes it necessary to adopt practices such as the inclusion of a winter cover crop (CC) between the income summer crops. In a soybean-soybean sequence, the effect of a cover crop of oats (Avena sativa L.) and vicia (Vicia sativa L.) on the contribution of carbon (C) through the dry matter (DM) produced, the available soil water (AUD) and the yield of the subsequent soybean crop were evaluated, considering environments differentiated by the slope. The treatments with CC (CCC) presented more AUD in soybean planting and ﬂowering, higher soybean yields and greater contributions of C to the system.